2015
DOI: 10.1158/1535-7163.mct-14-1061
|View full text |Cite
|
Sign up to set email alerts
|

On the Road to Precision Cancer Medicine: Analysis of Genomic Biomarker Actionability in 439 Patients

Abstract: Despite the increased use of molecular diagnostics, the extent to which patients who have these tests harbor potentially actionable aberrations is unclear. We retrospectively reviewed 439 patients with diverse cancers, for whom next-generation sequencing (mostly 236-gene panel) had been performed. Data pertaining to the molecular alterations identified, as well as associated treatment suggestions (on-or off-label, or experimental), were extracted from molecular diagnostic reports. Most patients (420/ 439; 96%)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
81
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 85 publications
(90 citation statements)
references
References 22 publications
6
81
0
2
Order By: Relevance
“…Although several prior studies examined the type/number of alterations and potentially actionable alterations by an approved drug or an experimental drug in clinical trial (16,29,30), fewer expanded their investigation to analyzing the responses and survival outcomes of patients who have been treated with drugs matching their aberrations. One of the first studies of this type was that of Von Hoff and colleagues (22), who investigated the use of molecular profiling tests to select patient's treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although several prior studies examined the type/number of alterations and potentially actionable alterations by an approved drug or an experimental drug in clinical trial (16,29,30), fewer expanded their investigation to analyzing the responses and survival outcomes of patients who have been treated with drugs matching their aberrations. One of the first studies of this type was that of Von Hoff and colleagues (22), who investigated the use of molecular profiling tests to select patient's treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, overall, 87 of our 347 patients (25%) were matched to therapy on the basis of their genomic results. We have recently shown that about 90% of patients have a theoretically actionable aberration (16). However, 56 of 347 patients (16%) were not evaluable because they succumbed to their disease shortly after their molecular profiling results were available, and many patients could not be matched because of the inability to access medication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a number of studies using whole-exome sequencing to provide diagnoses for undiagnosed, suspected genetic conditions, resulted in a roughly 25% success rate, with a significant proportion of these successes resulting in the identification of mutations that had not been previously characterized 40 . In "N of 1" cancer cases for both retrospective 41 and prospective studies 42 , finding actionable mutations that can affect treatment choices happens in well over 50% of the cases, with a high percentage of the actionable mutations identified as being de novo. We anticipate that future searches for individuals resilient to various genetic defects will be most effective when combining the traditional searches for positive outliers in known extended families with very broad searches for positive outliers in the general population.…”
Section: A R T I C L E Smentioning
confidence: 99%
“…Performing tumor biopsies remains the standard practice to establish cancer diagnosis and to detect potentially actionable alterations (1,2). However, tissue biopsies have limitations as they are invasive, expensive, and can expose the patient to pain and complications.…”
Section: Introductionmentioning
confidence: 99%